Selection, Realized Heritability, and Fitness Cost Associated With Dimethoate Resistance in a Field Population of Culex quinquefasciatus (Diptera: Culicidae) - Alam, Mehboob; Waqas Sumra, Muhammad; Ahmad, Daniyal; Shah, Rizwan Mustafa; Binyameen, Muhammad; Ali Shad, Sarfraz (Journal of economic entomology, 2017)
Mosquitoes are known to be vectors of numerous diseases leading to human morbidity and mortality at large scale in the world. Insecticide resistance has become a serious concern in controlling the insect vectors of public health importance. Dimethoate is an organophosphate insecticide used to control different insect pests including mosquitoes. Biological parameters of susceptible, unselected, and dimethoate-selected strains of Culex quinquefasciatus Say were studied in the laboratory to recognize resistance development potential and associated fitness cost. The dimethoate-selected strain showed 66.48-fold resistance to dimethoate compared with the susceptible strain after three continuous selections of generations. Realized heritability estimates of dimethoate resistance in Cx. quinquefasciatus yielded a value of 0.19. In dimethoate-selected strain, the biological traits including larval weight, survival from first instar to pupae, fecundity, number of next-generation larvae, relative fitness, net reproductive rate, intrinsic rate of natural increase, and biotic potential were significantly reduced as compared with the unselected strain. However, adult longevity, mean relative growth rate, weight of egg raft, female ratio, pupal duration, and emergence rate of the dimethoate-selected strain did not differ significantly compared with that of the unselected strain. This study provides useful information to devise retrospective management strategy for dimethoate resistance in Cx. quinquefasciatus.
Keywords: dimethoát; dědičnost; mosquito; Dimethoate; Male; resistance; kukla; mužské pohlaví; Insecticides; selection; Selection, Genetic; Culex; Pupa; ženské pohlaví; zvířata; genetická zdatnost; larva; insekticidy; selekce (genetika); Larva; Heredity; fitness cost; Insecticide Resistance; organophosphate; rezistence k insekticidům; Female; Genetic Fitness; Animals